1971
DOI: 10.1139/e71-083
|View full text |Cite
|
Sign up to set email alerts
|

The Hudsonian Orogeny Near Flin Flon, Manitoba: A Tentative Interpretation of Rb/Sr and K/Ar Ages

Abstract: Whole rock Rb/Sr age dating near Flin Flon, Manitoba, yields isochrons of 1775 89 m.y. for the Amisk Group (mainly volcanic rocks), and 1805 + 14 m.y. for the granodioritic Annabel Lake Pluton which intrudes the Amisk. These are considered t o be emplacement ages (within their errorlimits).A tentative interpretation of the Hudsonian Orogeny in this area is derived by fitting the Rb/Sr ages and previously published K/Ar ages to the sequence of events as determined from detailed structural studies. According to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1972
1972
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…gestion reported earlier by Sinha (1970) and confirmed by Rb-Sr whole rock analyses by Mukherjee et al (1971). The latter found that volcanic rocks near Flin Flon yielded an isochron of 1775 -C 89 m.y.…”
Section: Stall Lakesupporting
confidence: 70%
“…gestion reported earlier by Sinha (1970) and confirmed by Rb-Sr whole rock analyses by Mukherjee et al (1971). The latter found that volcanic rocks near Flin Flon yielded an isochron of 1775 -C 89 m.y.…”
Section: Stall Lakesupporting
confidence: 70%
“…[28] GBS can also operate as an independent process, and this can be accommodated by pumping out intragranular dislocations (from triple junctions that impede sliding), which glide to the opposite boundary and are eliminated by climb into the grain boundary (Figure 7d). Although the process was modeled originally by considering the simultaneous sliding of multiple grains by Ball and Hutchison, [29] it was modified later by Mukherjee [30] to consider sliding along individual grain boundaries. Langdon [31] developed a broad unified approach of GBS in coarse-grained and fine-grained materials and obtained the following expression for the superplastic strain rateε GBSÀSP in fine-grained materials, shown schematically in Figure 7ḋ…”
Section: The General Characteristics Of Superplastic Flowmentioning
confidence: 99%
“…He concluded that the rocks containing the deposit are Aphebian in age, and he accepted the Rb-Sr isochron age of 1750 ± 80 m.y. of Mukherjee et al (1971). At the Universities of Saskatoon and Alberta, zircon studies on the associated volcanic rocks are corroborating the approximate age of 1800 m.y.…”
mentioning
confidence: 71%